Secure video transcoding in mobile cloud computing - Baharon, Mohd Rizuan; Zainal Abidin, Zaheera; Abdollah, Mohd Faizal; Idris, Ariff; Abu, Nur Azman (Research Institute for Intelligent Computer Systems, 2018)
Video Transcoding is one of the recent services available online nowadays provided by the clouds to enable a user to convert a video format from one into another in a very convenient way. To transcode a video, all of the video contents need to be uploaded to the cloud storage. However, outsourcing video contents that may contain sensitive information do not guarantee the video security and privacy as the clouds have the ability to access them. Thus, in this paper, an enhanced homomorphic encryption scheme is proposed to allow massive amount of frames to be transcoded by the cloud server in a secure manner. This scheme encrypts integers rather than individual bits so as to improve the scheme’s efficiency. With the aid of a proposed process for multiple parties to communicate securely, the efficiency of the scheme is thoroughly evaluated and compared with related works. The result shows that our scheme offers much better efficiency, which makes it more suitable for operating the video transcoding in cloud environment